Ecoturismo e conservação ambiental na percepção da comunidade local e de visitantes: o caso de Alter-do-Chão, Pará, Brasil - SANTOS, Samara Figueiredo dos (Universidade Federal do Oeste do Pará, 2024)
Ecotourism is seen as a segment of tourism that makes sustainable use of the natural and cultural heritage, and motivates conservation in search of the formation of an environmentalist conscience. Therefore, this work aims to know how the practice of ecotourism activities at APA Alter do Chão has contributed to the conservation of the place and what has been its influence on the local economy in the perception of local workers and visitors. The research was conducted in the village of Alter do Chão, considered as an Environmental Protection Area (APA). The method used was a Case Study, whose approach was based on quantitative / qualitative. The instrument consisted of applying a structured interview, directed to tourists who were visiting the site, and workers, such as catraieiros, owners of tour agencies, motorboat drivers, and tour guides, who develop ecotourism activity in Alter do Floor. Thirty questionnaires were applied to the workers, and 30 directed to tourists, totaling a universe of 60 respondents. Data obtained through content analysis showed that the main perception of workers is associated with income generation. Moreover, the natural beauty attributed to appreciation of the environment has given great importance in assessing the APA Alter do Chão, so it's essential care regarding the characteristic features of this landscape. On the other hand, the lack of commitment to the environment is one of the factors that cause its degradation, so the adoption of information that allows the internalization of correct environmental practices enables the preservation and sustainability of the site. There are weaknesses about practices that strengthen the conservation of Alter do Chão APA, as most respondents expressed dissatisfaction when asked about the conservation of the site.